Challenging concepts in obstetrics and gynaecology : cases with expert commentary - Hezelgrave, Natasha; Abbott, Danielle; Shennan, Andrew H. ([Oxford] : Oxford University Press, 2015)
This is a case-based guide to difficult scenarios faced in the fields of obstetrics and gynaecology. Each case is set off by an'Expert Commentary' written by an expert, giving the reader both a solid base of knowledge and a nuanced view of current challenges.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 24, 2016).
Keywords: Gynecology -- Case studies; Obstetrics -- Case studies